Intermediate Accounting. V.1 - Dukes, Roland E.; Davis, Charles J.; Welsch, Glenna A.; Dyckman, Thomas R. (USA : IRWIN, 1992)
Contents of this book include: Foundation and review; Asset recognition and measurement 281; Owners'equity; Spcial topic.
Keywords: Accounting; Intermediate Accounting